Peningkatan Hasil Belajar Matematika Peserta Didik dengan Menggunakan Pendekatan Saintifik di Kelas I.A SD Negeri 04 Payakumbuh T.P 2021 / 2022 - Elfida Deswita (Departement of Mathematics Education, 2022)
This study aims to obtain data and information about how to increase students' mathematics learning outcomes using a scientific approach in class I.A SD Negeri 04 Payakumbuh TP. 2020/2021. The type of research that the authors did was Classroom Action Research (CAR). The subjects in the Classroom Action Research (PTK) that the author did were Class I.A students at SD Negeri 04 Payakumbuh, totaling 30 students with a composition of 12 boys and 18 girls. The procedure and flow of this research consists of three cycles with four research stages. Data collection instruments in this classroom action research include: knowledge tests, skill test sheets, documentation. Data collected in each observation activity from the implementation of the research cycle were analyzed descriptively using the percentage technique to see trends that occur in learning activities. The results of the research activities that have been carried out for two cycles, and based on all the discussions and analyzes that have been carried out, it can be concluded that: The increase in learning Mathematics through a scientific approach is marked by an increase in the learning completeness of students in each cycle, this can be seen from the stages of the scientific approach: Centered learning on students. Learning forms students' self concept. Learning avoids verbalism. Learning provides opportunities for students to assimilate and accommodate concepts, laws, and principles. Learning encourages an increase in students' thinking skills. Learning increases student learning motivation and teacher teaching motivation. Provide opportunities for students to practice communication skills. There is a process of validation of the concepts, laws, and principles constructed by students in their cognitive structure.